Reconfigurable and flexible voltage control strategy using smart PV inverters with integrated energy storage for advanced distribution systems. Issue 1 (30th September 2019) - Shuvra, Mahfuz A.; Chowdhury, Badrul
Abstract : A novel circuit topology is proposed for utility‐owned photovoltaic (PV) inverters with integrated battery energy storage system (BESS) and compared to two state‐of‐the‐art configurations. The proposed topology offers flexibility and can be applied to a range of distribution networks for tight voltage regulation. During BESS maintenance, the solar‐storage system reconfigures itself for a self‐run mode of operation, and actively compensates high penetration induced voltage fluctuation without activating overcurrent protection of the inverter, which is an added advantage of this strategy. This advantage is achieved by slightly increasing the inverter size to reserve a portion of inverter's current‐carrying capability. A dynamic model of the new configuration is also developed to analyse its performance in providing fast response for high ramp up/down solar irradiance variation. As the proposed control strategy is implemented at the device level, the local voltage regulation is quite guaranteed to be in the permissible range. Results from the analysis performed on a modified IEEE 33 bus medium voltage distribution network with multiple inverters show evidence that the proposed strategy has the potential to mitigate voltage fluctuation in several extreme cases.